PEMBERDAYAAN KELOMPOK PETANI JERUK DI KABUPATEN BARITO KUALA - Imelda, Sri; Rofi'i; huwaida, hikmayanti; Muhammad, Said (Jurnal IMPACT: Implementation and Action, 2023)
Barito Kuala Regency is an orange-producing center in South Kalimantan. This Banjar Siamese orange (Citrus reticulata) tastes sweet and sour fresh and many people, especially in South Kalimantan, love this orange. As one of the horticultural commodities that is one of the main sources in improving the economy of its citizens and has high economic value and makes a great contribution to the national economy. The Siamese orange that is most developed by farmers is Siamese orange. This is because Siamese oranges have ease of care and oranges are produced more and fresher. The partners of this PKM activity are the Citrus Farmer Partners of Sungai Gampa Asahi Village, Rantau Badauh District, Barito Kuala Regency. The problems faced by partners are limited farmer capital, direct citrus marketing to collectors/middlemen, and marketing is not yet online. The solutions offered consist of limited farmer capital, direct marketing of citrus to collectors/middlemen, and marketing that has not yet been marketed online using social media. The method of implementing this service is in the form of training on capital management, studies on crop marketing and marketing using social/online media. Community Empowerment Program service activities have been carried out well. Partners feel very helped by the PPM activities carried out because they can synergize with partners as orange farmers. In this activity, assistance was handed over in the form of agricultural support equipment to the Gampa Asahi River Village Orange Farmer Partners. in the form of FALCON Lawn Mower - Brush Cutter FC – 328. Keywords: Siamese Orange, Capital, Marketing, Social Media